Diversidade genética, produção de frutos e composição química em Schinus erebinthifolius Raddi - Souza, Danilla Cristina Lemos (2012)
The aroeira (Schinus terebinthifolius Raddi.) is a species of agro-industrial value, hue the potential proprieties of its essential oils for use in cosmetics, phytotherapics and in food industry. Facing conditions of devastation which are the natural Forest in Brazil, multidisciplinary studies of native species of economic value are important to establish the conservations management. In addition, those studies permit the indication of potential individuals for utilization in recuperation projects in degraded areas, and to establish commercial plantations. Because of the intensive exploration of aroeira in the low region of São Francisco River in Sergipe, this work was carried out with the objective of characterize individuals in accord with genetic diversity, chemical essential oil profile, yield of fruits, and morphophysiological characterization of seeds. For genetic diversity characterization it was utilized the ISSR molecular marker. The chemical characterization was carried out by GC-MS, obtaining chemical profiles of the fruits essential oils. The yield of fruits was estimated by Fournier methodology, and the seed viability evaluated by germination tests. The existence of variation in genetic profile, chemical characterization, and seed morphophysiological characterization is utile for diversity characterization aiming the aroeira conservation. The variations can be utilized for tree-matrix selection for forest restoration and in plant breeding projects. This species has suffering with the consequences of the forest fragmentation and emerge as an alternative for agriculture diversification, meanly because the species is prominent organic products as pink pepper which deserves attention.